Does gender affect immune response in HIV patients? - SahingÃ¶z Erdal, Gulcin; IsÄ±ksacan, Nilgun; Korkusuz, Ramazan; Kasapoglu, PÄ±nar; Kart Yasaroglu, Kadriye (Jurnal Teknologi Laboratorium, 2021)
Gender differences affect the frequency and course of many diseases. This study aimed to determine the gender distribution in HIV-infected patients and investigate the relationship between gender and immune response. The study included HIV-infected patients who followed up in our hospital in 2018. The patients were divided into HIV RNA negative patients (Group 1) and HIV RNA positive patients (Group 2). Patients with diseases that may affect the immune system and those using drugs that affect the immune system were excluded from the study. The evaluation was made of 549 patients, as 305 patients (45 females 14.75%) in Group 1 and 224 patients (23 females, 9.43%) in Group 2. When the CD4/CD8 ratio of male and female patients was compared in both groups, a lower rate was determined in females (0.71-0.58) than males (0.82-0.93). A negative correlation was determined between HIV RNA and the CD4/CD8 ratio in premenopausal females (p=0.045) and males (â‰¤45 years p=0.0001). Clinical studies of HIV infection have demonstrated better initial viremia control in females with primary infection, faster disease progression, and stronger immune activation than males for the same level of viral replication.